Access and mobility management technologies for 6G satellite communications network - Xiaowen WU; Xiang LING; Lidong ZHU; Zhenfeng JIAO; Jian CHENG; Bo YANG (Dianxin kexue)
Analsisand outlook for satellite communication access and mobility management technology in 6G network was presented.Firstly, the access technology of current global representative satellite mobile communications system was introduced, as well as the international standardization organization research status of 5G NR satellite access technology.According to the challenges for 6G satellite communications network access, some solutions regarding to 6G satellite communications access were proposed respectively from the aspects of extremely simple access, extremely intelligent access.Furthermore, according to the demand of massive terminals handoff in the high dynamic scenario of 6G satellite communications, the flexible handoff scheme based on cloud channel technology, which supported batch massive terminals mobility management for across satellites and beams, was proposed.